2024
DOI: 10.7554/elife.87811
|View full text |Cite
|
Sign up to set email alerts
|

A concerted increase in readthrough and intron retention drives transposon expression during aging and senescence

Abstract: Aging and senescence are characterized by pervasive transcriptional dysfunction, including increased expression of transposons and introns. Our aim was to elucidate mechanisms behind this increased expression. Most transposons are found within genes and introns, with a large minority being close to genes. This raises the possibility that transcriptional readthrough and intron retention are responsible for age-related changes in transposon expression rather than expression of autonomous transposons. To test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The specific distribution of NET-seq reads suggested that Pol II-dependent Ea-IR -transcripts contain also XI-k mRNA sequences (Figure 5A). In animals, specific stressful conditions can trigger Pol II to read through termination sites, producing transcripts that include sequences from nearby transposons 51-53 . Similarly, we observed Pol II readthrough at the termination sites of XI-k , leading to the incorporation of Ea-IR sequences into Xl-k transcripts (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…The specific distribution of NET-seq reads suggested that Pol II-dependent Ea-IR -transcripts contain also XI-k mRNA sequences (Figure 5A). In animals, specific stressful conditions can trigger Pol II to read through termination sites, producing transcripts that include sequences from nearby transposons 51-53 . Similarly, we observed Pol II readthrough at the termination sites of XI-k , leading to the incorporation of Ea-IR sequences into Xl-k transcripts (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, excessive TE activation has been observed in senescent human cells and in response to aging in both Drosophila and mammals ( 101–104 ). Moreover, a recent analysis of RNA-seq datasets of senescent or aged cells in both humans and mice correlated increased transposon expression with transcriptional readthrough and intron retention ( 105 ).…”
Section: Discussionmentioning
confidence: 99%